STRATEGI PEMASARAN (4P) UMKM DALAM SITUASI PANDEMIC COVID-19 DI JURONG TENGKU FAKINAH GAMPONG PEUNITI KOTA BANDA ACEH - Tamitha Intassar Husen; Nabila Hilmy Zhafira; Ikhsan Ikhsan; Cut Devi Maulidasari; Ika Rahmadani (Universitas Teuku Umar, 2022)
Indonesia was attacked by a pandemic known as Coronavirus Disease 2019 (Covid-19) in early 2020.The number of cases and those who died was so fast that the government's step was to impose LargeScale Social Restrictions (PSBB). The policy taken by the government has made various sectors of lifeshaky because people have to stay at home, study at home, make transactions at home, and evenworship at home. This has an impact on business actors, especially Micro, Small and Medium Enterprises(MSMEs). Most of the people in Jurong Teungku Fakinah Gampong Peuniti Banda Aceh City actuallyalready know that they are still implementing health and marketing protocols. However, the marketingstrategy is the main obstacle to doing marketing. To control this problem, the servant took the initiative toprovide input, advice and training materials to the community regarding the marketing strategy (4P) ofMSMEs in this Covid-19 pandemic. The method of implementing this activity is in the form of materialpresentation, video presentation, and interactive discussion. The results of this activity are expected tofoster optimism in MSME actors in managing their business in the midst of a pandemic.Keywords: Covid-19, Micro, Small and Medium Enterprises (MSMEs), Marketing Strategy (4P)